Magnetotelluric Imaging of the Lithosphere Across the Variscan Orogen (Iberian Autochthonous Domain, NW Iberia) - Alves Ribeiro, J. (2019)
A new magnetotelluric (MT) survey comprising 17 MT soundings throughout a 30 km long N30°W transect in the Iberian autochthons domain of NW Iberia (Central Iberian Zone) is presented. The 2-D inversion model shows the resistivity structure of the continental crust up to 10 km depth, heretofore unavailable for this region of the Variscan Orogen. The MT model reveals a wavy structure separating a conductive upper layer underlain by a resistive layer, thus picturing the two main tectonic blocks of a large-scale D2 extensional shear zone (i.e., Pinhel shear zone). The upper layer represents a lower grade metamorphic domain that includes graphite-rich rocks. The lower layer consists of high-grade metamorphic rocks that experienced partial melting and are associated with granites (more resistive) emplaced during crustal thinning. The wavy structure is the result of superimposed crustal shortening responsible for the development of large-scale D3 folds (e.g., Marofa synform), later deflected and refolded by a D4 strike-slip shear zone (i.e., Juzbado-Penalva do Castelo shear zone). The later contribution to the final structure of the crust is marked by the intrusion of postkinematic granitic rocks and the propagation of steeply dipping brittle fault zones. Our study demonstrates that MT imaging is a powerful tool to understand complex crustal structures of ancient orogens in order to design future prospecting surveys for mineral deposits of economic interest.